2021
DOI: 10.1038/s41598-021-00374-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of intrinsic and extrinsic contributions to anisotropic magnetoresistance

Abstract: Electrical conduction in magnetic materials depends on their magnetization configuration, resulting in various magnetoresistances (MRs). The microscopic mechanisms of MR have so far been attributed to either an intrinsic or extrinsic origin, yet the contribution and temperature dependence of either origin has remained elusive due to experimental limitations. In this study, we independently probed the intrinsic and extrinsic contributions to the anisotropic MR (AMR) of a permalloy film at varying temperatures u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…[142,246,247] For instance, a UV-cured Ag 2 Se-based thermoelectric composite was fabricated using a 3D printer based on digital-light-processing techniques, achieving a power factor of ≈51.5 μW m −1 K −2 at room temperature. [31] Mallick et al reported a one-pot synthesis and processing of n-type Ag 2 Se-based screen-printed materials with mixed Ag and Se powder. [142] The targeted orthorhombic 𝛽-Ag 2 Se phase was formed via postprinting sintering at moderate temperature, thereby reducing the detrimental impacts of binder and solvent.…”
Section: Low-temperature Body Heat Recovery To Electric Powermentioning
confidence: 99%
See 1 more Smart Citation
“…[142,246,247] For instance, a UV-cured Ag 2 Se-based thermoelectric composite was fabricated using a 3D printer based on digital-light-processing techniques, achieving a power factor of ≈51.5 μW m −1 K −2 at room temperature. [31] Mallick et al reported a one-pot synthesis and processing of n-type Ag 2 Se-based screen-printed materials with mixed Ag and Se powder. [142] The targeted orthorhombic 𝛽-Ag 2 Se phase was formed via postprinting sintering at moderate temperature, thereby reducing the detrimental impacts of binder and solvent.…”
Section: Low-temperature Body Heat Recovery To Electric Powermentioning
confidence: 99%
“…[ 142,246,247 ] For instance, a UV‑cured Ag 2 Se‐based thermoelectric composite was fabricated using a 3D printer based on digital‐light‐processing techniques, achieving a power factor of ≈51.5 µW m −1 K −2 at room temperature. [ 31 ] Mallick et al. reported a one‐pot synthesis and processing of n‐type Ag 2 Se‐based screen‐printed materials with mixed Ag and Se powder.…”
Section: Emerging Thermoelectric Applicationsmentioning
confidence: 99%
“…The special aspect of the terahertz range is that σ ( ω ) is dominated by intraband contributions which are usually well approximated by the Drude peak, σ ( ω ) ∝ (1 − iωτ ) −1 , where τ is the transport relaxation time. It is then possible to split [15,193] AMR intoAMR=σσσ=A1iωτ+B.Since the ω -independent term B happens to be a function of the intrinsic AMR and the ω -dependent part of the extrinsic AMR, the ac-AMR offers a possibility for experimentally distinguish these two quantities (see §§1.1 and 3.1) [15]. In this fashion, Co, Ni, Ni 50 Fe 50 [15] and permalloy [15,193] were investigated (see §3.1 for the discussion).…”
Section: Applications and Further Topicsmentioning
confidence: 99%
“…It is then possible to split [15,193] AMR intoAMR=σσσ=A1iωτ+B.Since the ω -independent term B happens to be a function of the intrinsic AMR and the ω -dependent part of the extrinsic AMR, the ac-AMR offers a possibility for experimentally distinguish these two quantities (see §§1.1 and 3.1) [15]. In this fashion, Co, Ni, Ni 50 Fe 50 [15] and permalloy [15,193] were investigated (see §3.1 for the discussion). Please note that the frequency-dependence was not investigated by means of AC measurements, but the samples were instead subjected to an incident polarized electrical pulse in THz frequency.…”
Section: Applications and Further Topicsmentioning
confidence: 99%
“…This has boosted a renewed interest in the studies of the MR characteristics of ferromagnetic metals and alloys which constitute an important ingredient in all spintronic devices. Especially exciting are the recent experimental and theoretical achievements [14][15][16][17] in clarifying the microscopic mechanisms of the AMR and related magnetotransport phenomena by distinguishing between extrinsic and intrinsic contributions.…”
Section: Introductionmentioning
confidence: 99%